Mengungkap Makna Sejarah Nama Tempat: Studi Toponimi dan Pengaruh Kolonial di Asia dalam Manuskrip Serat Ngelmu Bumi Asia 1860 - Sumarlina, Elis Suryani Nani; Pawestri, Wening; Darsa, Undang Ahmad; Permana, Rangga Saptya Mohamad; Sudardi, Bani; Rasyad, Abdul (Universitas Hamzanwadi, 2025)
The study of toponymy and colonial influences in Asia in the SN manuscript is useful for making significant contributions to the understanding of toponymy, colonial influence, and historical context in Asia, especially through the lens of the Serat Ngelmu Bumi Asia 1860 manuscript. The purpose of this study is to analyze the history of place names that have been influenced by colonialism. Which places are written in the SNBA manuscript, namely a manuscript containing the geographical conditions of the Asian continent in 1860. The methods used in this study are literature study, philological research methods, and toponymy studies. The results of this study indicate that place names in Asia, especially those recorded in the SNBA manuscript of 1860, reflect significant colonial influence. Many place names recorded in the SNBA manuscript, such as India Depan, India Belakang, and Ceylon, show changes that occurred due to decolonization and foreign cultural influences. Changes in place names often reflect the dominance and political interests of the colonizers. The colonizers used new names or changed place names to show their power. The use of foreign languages ​​in place naming, often derived from the language of the colonizer, influences the way place names are identified and used.